Parallel Agile : faster delivery, fewer defects, lower cost /: faster delivery, fewer defects, lower cost. (2020) - Rosenberg, Doug; Boehm, Barry W; Stephens, Matt, 1971-; Suscheck, Charles; Dhalipathi, Shobha Rani; Wang, Bo
No abstract available